2002
DOI: 10.1111/j.1471-3802.2002.00170.x
|View full text |Cite
|
Sign up to set email alerts
|

Individualised educational programmes. Part I: a literature review

Abstract: This review was undertaken as part of a research project commissioned by the Scottish Executive and carried out by a team from Glasgow and Newcastle Universities between January 2000 and January 2001 when the report was published (Banks et al., 2001). The research study, entitled ‘Raising the Attainment of Pupils with Special Educational Needs’, followed the issuing of new guidelines (SOEID, 1998a; SEED, 1999) which linked the use of individualised educational programmes (IEPs) to the wider political enterpris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…My observations suggested that teachers select targets which are very specific to subject areas and these are often worked towards in intervention groups with support staff. This makes application across all teaching and learning challenging and risks reductionism (Millward et al ., 2004, p. 5).…”
Section: Presentation and Analysis Of Findingsmentioning
confidence: 99%
“…My observations suggested that teachers select targets which are very specific to subject areas and these are often worked towards in intervention groups with support staff. This makes application across all teaching and learning challenging and risks reductionism (Millward et al ., 2004, p. 5).…”
Section: Presentation and Analysis Of Findingsmentioning
confidence: 99%
“…By documenting the "ideal scenario" teachers can put in the right support for the individual student´s reading needs. Furthermore, the legitimacy of NPM is that teachers' work will be more transparent so that "inefficient teachers" can be held accountable by stakeholders such as the parents (Millward et al, 2002). For example, if a teacher fails to document a student with reading difficulties, then the parents can hold the teacher accountable for not documenting.…”
Section: An Organizational Approach To Documentation Of Special Educamentioning
confidence: 99%
“…It also shows that the personal reviews in these plans are plentiful and how these descriptions can affect children's identity constructs (Andreasson, 2007;Vallberg Roth & Månsson, 2008). Results from both international and national studies show that the documents often focus on individual shortcomings and deficiencies and the interventions they guide have their roots in behavioural psychology (Millward et al, 2002;Isaksson et al, 2007;Vallberg Roth & Månsson, 2008;Swedish School Inspectorate, 2012). In an international meta study of almost 300 studies, Mitchell et al (2010) demonstrated that there is some general criticism of the plans that seems to recur in different contexts.…”
Section: Institutionalised Assessment Practices In Swedenmentioning
confidence: 99%